Identification of influential patterns of sulfitation treatment of sugar production thick juice and remelt on the beet sugar quality - V. O. Gorodetsky; S. O. Semenikhin; N. M. Daisheva; N. I. Kotlyarevskaya (Новые технологии, 2022)
It is well known that in order to obtain crystalline sugar of a high quality category (Extra and TS1), it is necessary to ensure the production of concentrated sugar-containing intermediates with the lowest possible color, since it is these intermediates that directly determine the color of the resulting crystalline sugar. Laboratory studies have been carried out on the effect of sulfitation treatment using various reagents, namely, sulfurous anhydride and sodium bisulfite, of concentrated intermediates – thick juice and remelt syrup B+C of sugar production on the quality of beet sugar. It has been established that the sulfitation treatment of concentrated intermediates using sulfur dioxide provides a greater reduction in their color compared to sodium bisulfite – from 996,70 to 830,30 and 857,30 ICUMSA units respectively. It has been established that sulfitation treatment with using various reagents of concentrated intermediates provides a decrease in the color of sugar. So, according to the color index, sugar obtained in laboratory conditions from samples obtained using sulfitation treatment, according to the requirements of GOST 33222-2015, corresponds to category TS1, and obtained from an untreated sample, to category TS2. Thus, in a critical situation, sulfitation treatment can provide sugar with a higher quality category. It has been established that during long-term storage (up to 100 days) of concentrated sugar-containing intermediates, their color increases, however, preliminary sulfitation treatment using sulfur dioxide provides the smallest increase in color during storage, compared with treatment with sodium bisulfite. The increase in color after 100 days of storage relative to the initial values was 18,46 and 36,26%, respectively.